Physical Activity, Sedentary Behavior, and Fitness Levels in University Students - Mega Amanda; Reyna Wildan Firdaus Azis; Aditya Dwi Santoso; Hoirun Nisa (Epidemiology and Society Health Review (ESHR), 2026)
Background: Physical fitness is crucial for university students as it supports productivity and helps prevent disease. It largely depends on levels of physical activity and sedentary behavior. However, the current student lifestyle relies heavily on technology, resulting in reduced physical activity and increased sedentary behavior. This study aims to investigate the physical activity, sedentary behavior, lifestyle, and physical fitness of university students. Method: This cross-sectional study was conducted using purposive sampling on active students of UIN Syarif Hidayatullah Jakarta from the 2020-2022 batch. Results: The findings showed that half of the students (51.6%) had low (normal) sedentary behavior, while a substantial proportion (45.1%) had moderate sedentary levels. Additionally, 32.9% of students were classified as having poor physical fitness, and most students (57.3%) reported low levels of physical activity. Conclusion: A higher proportion of students demonstrated poor physical fitness, moderate levels of sedentary behavior, and low levels of physical activity. These findings highlight the importance of improving physical fitness through regular exercise and reducing sedentary behavior, particularly non-essential smartphone use. In addition, the university should consider developing and implementing policies that encourage greater physical activity among students, helping them achieve optimal fitness to better support their daily activities.